Advances in Nanotechnology-Based Immunotherapy for Glioblastoma - Tang, Lin; Zhang, Ming; Liu, Chaoyong (Frontiers in Immunology, 2022)
Glioblastoma (GBM) is the most aggressive type of brain tumor. Despite the multimodal therapies, the effectiveness of traditional treatments is not much satisfying. In recent years, immunotherapy has become the focus of tumor treatment. Unlike traditional treatments that directly target tumor cells, immunotherapy uses the body’s immune system to kill tumors. However, due to the severe immunosuppressive microenvironment of GBM, it generally has a poor response to immunotherapy. In addition, the existence of the blood-brain barrier (BBB) also compromises the immunotherapeutic efficacy. Therefore, effective immunotherapy of GBM requires the therapeutic agents to not only efficiently cross the BBB but also relieve the strong immunosuppression of the tumor microenvironment of GBM. In this review, we will first introduce the CNS immune system, immunosuppressive mechanism of GBM, and current GBM immunotherapy strategies. Then, we will discuss the development of nanomaterials for GBM immunotherapy based on different strategies, roughly divided into four parts: immune checkpoint therapy, targeting tumor-associated immune cells, activating immune cells through immunogenic cell death, and combination therapy, to provide new insights for future GBM immunotherapy.